KONFIRMASI LIMA FAKTOR YANG MEMPENGARUHI KUALITAS HIDUP REMAJA PUTRI TINGKAT SMA - Rina Dwi Anggraeni,; Euis Atikah, (Journal of Innovation Research and Knowledge, 2023)
The Quality of life of young women either if the variables that influenced him including menstrual cycle on young women walking with regular and balanced. This research aims to know the direct and indirect influence as well as the adjustment is the home environment, the interaction patterns of adolescent-parent, physical activity, stress levels, and the menstrual cycle towards the quality of life of young women in Rengasdengklok SMAN 1 the year 2016. With the method of quantitative approaches that use design cross sectional. The sample used 54 teenager. The method of analysis by SEM analysis using Smart-PLS 2.0 and SPSS. The results of testing a hypothesis produce the percentage of influence all variables to the quality of life the young women in this model of 74.67% and the rest from other variables, on the variables examined direct influence of 74.50% and not influence direct of 0.17%. The value of the Q-Square (predictive relevance) of 93.92%, this means that the representative model was able to explain the diversity as well as being able to examine a phenomenon that is in this research. From the results of research that has been done, the researchers suggested that in a home environment in particular components of the behavior of the occupants more enhanced insight or discipline in keeping the environment clean house, because on this research suggests that the health of the home environment in particular components of the behavior of the occupants is still low